INTERAKSI FRAKSI DALAM PROSES PENGAMBILAN KEPUTUSAN PUBLIK (Studi Organisasi DPRD Kota Malang 2010, Atas Kasus Pasar Tradisional Dinoyo Dan Blimbing Menjadi Pasar Moderen Di Kota Malang) - Nedo, Maria Susana (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
Abstract:This study aimed at describing the interaction of the factions in the organization's decision-making process DPRD Malang; with a focus on the kind of interaction both internally and externally fraction of the party over government policies Malang in development projects / peralian traditional market status and Dinoyo Blimbing Malang into Modern market in the city of Malang. Based on the results of field research (Member of Parliament Malang in Malang Parliament Office II) and analysis of data regarding political interactions between members of the board in a fraction in DPRD Malang; especially the interactions between the factions with regard to public decision making (policy Making) in the case of market Dinoyo and Blimbing can be seen the political interaction between the factions in the organization DPRD Malang in various forms, including: conflict, Accommodation, Compromise, and the Coalition in the process of pushing or thwart development policy and the transitional status of both markets.Although the final decision through voting; DPRD Malang still approve policies Dinoyo market development and market Blimbing as the modern market, since the beginning of the discussion on the construction of two projects in the city parliament Malang occur Pros and Cons of each-each faction will be the plan. Semuannya behalf of the interests of the people to remain grounded in their respective party platforms. The difficulties in the market building approvals showed adannya interaction among factions in the party's internal and external parties on development projects in both markets. The change of final views and policies fractions as a result of lobbying-lobbying in the political interaction between factions both in the form of cooperation (Pro) and the opposition (Counter) shows the form of interaction in political communication who conducted members of the faction DPRD Malang internal and external parties resulting in a decision together though through a vote to approve the construction of traditional markets and Dinoyo Blimbing into Modern market.Â Keywords: Fraction of DPRD II Malang, Interaction and Political Communication, Public Decision